2012
DOI: 10.1007/s12098-012-0879-5
|View full text |Cite
|
Sign up to set email alerts
|

Common Childhood Poisonings and Their Outcome in a Tertiary Care Center in Delhi

Abstract: Clinical profile of children presenting with poisoning to the Pediatric emergency department of a tertiary care hospital in Delhi from 8.1.2009 to 8.10.09 was studied prospectively. Fifty two cases of accidental poisoning were reported during this period which formed 1.05 % of all pediatric admissions (5094 admissions). No case of homicidal poisoning was reported. There were 80.7 % children between 1-5 y of age with male preponderance. PICA was observed in 57.7 % children. Overall mortality was 7.7 % and 11.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 3 publications
7
15
2
Order By: Relevance
“…Available reports state poisoning as accidental in children admitted with h/o poisoning [3,12,[17][18][19][20]. In our study, AP accounted for 1.7% pediatric admissions in accordance with observation of GhoshVB et al [21] Kouéta F et al [22] noted rate of hospitalization for acute AP as 1.3%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Available reports state poisoning as accidental in children admitted with h/o poisoning [3,12,[17][18][19][20]. In our study, AP accounted for 1.7% pediatric admissions in accordance with observation of GhoshVB et al [21] Kouéta F et al [22] noted rate of hospitalization for acute AP as 1.3%.…”
Section: Discussionsupporting
confidence: 89%
“…Accidental poisoning in pediatric age group is commonly seen in <5 yrs [3,18,[21][22] and more frequent among 1-3 years group. [3,11,19].…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to that in other studies that showed kerosene to be the leading source of poisoning in children. [10,11] The study also showed that children <3 years of age were more commonly involved in childhood poison ing (74.3%). Studies by Abbas et al [12] showed simi lar findings, with children <3 years hav ing the highest incidence of poisoning (46.5%) in their study sample.…”
Section: Discussionmentioning
confidence: 87%
“…Ghosh VB et al, showed that 80.7% of poisoning in the age group 1-5 years [6]. Sarkar AK et al, showed that out 134 cases children belong to age group of 1-3 years are main victims [7].…”
Section: Discussionmentioning
confidence: 99%